Melt‐Centrifuged (Bi,Sb)2Te3: Engineering Microstructure toward High Thermoelectric Efficiency - Pan, Yu; Aydemir, Umut; Grovogui, Jann A.; Witting, Ian T.; Hanus, Riley; Xu, Yaobin; Wu, Jinsong; Wu, Chao‐Feng; Sun, Fu‐Hua; Zhuang, Hua‐Lu; Dong, Jin‐Feng; Li, Jing‐Feng; et al. (Advanced materials (Weinheim), 2018)
Microstructure engineering is an effective strategy to reduce lattice thermal conductivity (κl) and enhance the thermoelectric figure of merit (zT). Through a new process based on melt‐centrifugation to squeeze out excess eutectic liquid, microstructure modulation is realized to manipulate the formation of dislocations and clean grain boundaries, resulting in a porous network with a platelet structure. In this way, phonon transport is strongly disrupted by a combination of porosity, pore surfaces/junctions, grain boundaries, and lattice dislocations. These collectively result in a ≈60% reduction of κl compared to zone melted ingot, while the charge carriers remain relatively mobile across the liquid‐fused grains. This porous material displays a zT value of 1.2, which is higher than fully dense conventional zone melted ingots and hot pressed (Bi,Sb)2Te3 alloys. A segmented leg of melt‐centrifuged Bi0.5Sb1.5Te3 and Bi0.3Sb1.7Te3 could produce a high device ZT exceeding 1.0 over the whole temperature range of 323–523 K and an efficiency up to 9%. The present work demonstrates a method for synthesizing high‐efficiency porous thermoelectric materials through an unconventional melt‐centrifugation technique. The melt‐centrifugation technique is demonstrated to be able to decrease the thermal conductivity while preserving the good electrical properties. By introducing a unique porous structure with microscale dislocation, ≈60% reduction in lattice thermal conductivity compared to conventional zone melted ingots is achieved. Such a method paves a new way for top‐down introduction of large porosity and dense dislocations in bulk materials.